1988
DOI: 10.1073/pnas.85.5.1412
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of prostaglandin G/H synthase from sheep vesicular gland determined from the complementary DNA sequence.

Abstract: Prostaglandin G/H synthase (8,11,14-icosatrienoate,hydrogen-donor:oxygen oxidoreductase, EC 1.14.99.1) catalyzes the first step in the formation of prostaglandins and thromboxanes, the conversion of arachidonic acid to prostaglandin endoperoxides G and H. This enzyme is the site of action of nonsteroidal anti-inflammatory drugs. We have isolated a 2.7-kilobase complementary DNA (cDNA) encompassing the entire coding region of prostaglandin G/H synthase from sheep vesicular glands. This cDNA, cloned from a AgtlO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(176 citation statements)
references
References 39 publications
4
170
1
1
Order By: Relevance
“…COX is bifunctional, converting arachidonic acid (AA), an omega-6 fatty acid, to the precursor prostaglandin G 2 (PGG 2 ) and subsequently converting PGG 2 to the precursor PGH 2 via cyclooxygenase and peroxidase activities, respectively. Three isoforms of COX have been found -the constitutively expressed COX-1 [5][6][7]; COX-2, which can be inducible or constitutive, depending on the tissue [1,[8][9][10]; and the constitutively expressed COX-3, which is believed to be a splice variant of COX-1 [11]. Although COX-1 is considered the housekeeping enzyme expressed in nearly all tissues, COX-2 is generally perceived to be involved in pathological conditions, such as inflammation and cancer [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…COX is bifunctional, converting arachidonic acid (AA), an omega-6 fatty acid, to the precursor prostaglandin G 2 (PGG 2 ) and subsequently converting PGG 2 to the precursor PGH 2 via cyclooxygenase and peroxidase activities, respectively. Three isoforms of COX have been found -the constitutively expressed COX-1 [5][6][7]; COX-2, which can be inducible or constitutive, depending on the tissue [1,[8][9][10]; and the constitutively expressed COX-3, which is believed to be a splice variant of COX-1 [11]. Although COX-1 is considered the housekeeping enzyme expressed in nearly all tissues, COX-2 is generally perceived to be involved in pathological conditions, such as inflammation and cancer [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…COX-1 is a well-characterized, constitutively expressed enzyme originally purified from ovine and bovine vesicular glands and platelets (Smith, 1992;Smith et al, 1991). The cDNA clones of the 2.8-kb COX-l mRNA isolated from ovine (DeWitt and Smith, 1988), murine (DeWitt et al, 1990) and human tissues (Funk et al, 1991) encodes a protein of approximately 600 amino acids in length. The cDNA clones of the 4.4-kb COX-2 message have been isolated from various tissues of human and animal origin and also encode a protein of about 600 amino acids (Fletcher et al, 1992;Hla and Neilson, 1992).…”
mentioning
confidence: 99%
“…[7][8][9] The effects of the PTGDR on asthma were shown with a mouse study; the asthmatic symptoms of PTGDR À/À mice were improved compare with wild-type mice. 8 In addition, PGD2 15 and LTC4 16,17 are both derived from arachidonic acid. However, the relationship between the PTGDR and responsiveness to a LTRA has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] However, the results of a recent study showed that PGD2 activated eosinophils and enhanced LTC4 synthesis in vivo. 18 Accumulating evidence suggests that the cysteinyl leukotrienes (cysLTs) are the primary mediators of exercise-induced bronchoconstriction (EIB), as demonstrated by the detection of cysLTs in the airways, 19 increased levels of urinary leukotriene E4 20 and increased levels of cysLTs in exhaled breath condensates, 21 and in induced sputum 22 from children with EIB.…”
Section: Introductionmentioning
confidence: 99%